2018
DOI: 10.4067/s0716-10182018000600731
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis e hipoacusia por manipulación de carne porcina

Abstract: Meningitis and hypoacusia due to swine meat handling Zoonotic meningitis by Streptococcus suis has been described occasionally in Chile and linked to pig farmers in the south of the country. We report a female case that developed acute bacterial meningitis by this agent, two days after handling a piece of raw swine meat. She did not participate on swine breeding nor visited farms. Diagnosis was obtained by CSF culture. A severe hearing loss and not recovered despite corticosteroids use and antimicrobial treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Streptococcus pneumoniae, Haemophilus influenzae and Neisseria are the main bacterial pathogens responsible for acute bacterial meningitis (9,10) and it is reported that the host genetic factors are the major determinants of susceptibility for bacterial meningitis (7). Recently, zoonotic meningitis has been occasionally linked to pig farmers who have developed acute bacterial meningitis after handling raw swine meat (11). At present, there remains an incomplete understanding of the pathogenesis and the best methods for the prevention and treatment of bacterial meningitis and further research looking at the pathogenesis of bacterial meningitis is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae, Haemophilus influenzae and Neisseria are the main bacterial pathogens responsible for acute bacterial meningitis (9,10) and it is reported that the host genetic factors are the major determinants of susceptibility for bacterial meningitis (7). Recently, zoonotic meningitis has been occasionally linked to pig farmers who have developed acute bacterial meningitis after handling raw swine meat (11). At present, there remains an incomplete understanding of the pathogenesis and the best methods for the prevention and treatment of bacterial meningitis and further research looking at the pathogenesis of bacterial meningitis is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Infection in humans presents clinically as meningitis, endocarditis, septicemia, and/or arthritis, and thus far is primarily reported in Asia [3,4]. It is rarely observed in western regions, such as Argentina and the United States [5,6].…”
Section: Introductionmentioning
confidence: 99%